PENGGUNAAN EKSTRAK BIJI KLUWEK (Pangium edule Reinw.) SEBAGAI INSEKTISIDA NABATI TERHADAP MORTALITAS KECOAK (Blatella germanica L.) - Hidayat, Saleh (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2014)
Kluwek (Pangium edule Reinw.) has many advantages, one of the advantages is as the material of insecticide by using cyanide acid that was toxic in seed. It needed the evidence to prove the advantages is as the material of insecticide of kluwek seed toward organism which was sensitive with cyanide acid material. The organism which was used: roach (Blatella germanica L.). The problems of this study were did the use of the extract kluwek seed (Pangium edule Reinw.) as the plants insecticide toward mortality of the roach (Blatella germanica L.). The method of this study has experimental method with Completely Randomized Design (CRD) at the six treatments and four replications, Duncan Multiple Range Test (DMRT) with SPSS version 16.0 programs. The result of this study were kluwek seed had significance effect toward mortality of roach (Blatella germanica L.) in the treatment (P5) with concentrate (125%). The roach was dead in twelve hour average. It means that (1) Use of the extract of kluwek seed as the plants insecticide with concentrate among 25%, 50%, 75%, 100% and 125% had significance effect toward mortality of the roach (Blatella germanica L.).Â Key words: mortality, kluwek seed, and roach